A kind of asparagus polyurea based in-situ polymer electrolyte material and its preparation method and application

By using asparagus polyurea as the matrix and combining in situ polymerization process and polyetheramine structure soft chain, the problem of low electrolyte interface reaction and conductivity in solid-state batteries is solved, and efficient battery cycle stability and ionic conductivity are achieved. Suitable for solid-state battery applications.

CN118852582BActive Publication Date: 2025-01-14CENT SOUTH UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411303790.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-14
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The interface reaction of existing solid-state electrolytes is difficult to control when high-energy negative electrodes such as silicon negative electrodes and lithium metal negative electrodes, resulting in the impact of battery cycling performance. The ionic conductivity of all-solid polymer electrolytes is low, which cannot meet the application needs of solid-state batteries.

Method used

Asparagus polyurea is used as the matrix, and the polyetheramine structure soft chain is combined through in-situ polymerization process to improve mechanical properties and ionic conductivity. Liquid electrolyte is used as a plasticizer to improve the contact problem of electrolyte/electrode interface and improve ionic conductivity. Rate.

Benefits of technology

It effectively inhibits the growth of dendrites in the battery, improves the cycle life, significantly improves the ionic conductivity of asparagus polyurea-based polymer electrolyte, solves the problem of low ionic conductivity of electrolytes in all-solid-state batteries, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852582B_ABST
    Figure CN118852582B_ABST
Patent Text Reader

Abstract

The present invention discloses an asparagine polyurea-based in-situ polymer electrolyte material and a preparation method and application thereof. The electrolyte material is obtained by in-situ polymerization of raw materials including polyaspartic acid ester, isocyanate curing agent and electrolyte; the molar ratio of the amino group in the polyaspartic acid ester to the isocyanate group in the isocyanate curing agent is 1:0.8~1.2; the mass ratio of the polyaspartic acid ester to the electrolyte is 1:1~2; the electrolyte contains sodium salt, solvent and additives, and the solvent is a small molecule plasticizer. The material is obtained by adding polyaspartic acid ester and isocyanate curing agent to the electrolyte in sequence, mixing them thoroughly and then heating them for in-situ polymerization reaction. The material adopts in-situ polymerization of asparagine polyurea, which effectively improves the electrode / electrolyte interface compatibility and improves the battery cycle life, while also increasing the ionic conductivity of the electrolyte to 1.34×10 ‑3 S cm ‑1 , which can meet the performance requirements in solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer electrolyte material, in particular to an asparagine polyurea-based in-situ polymer electrolyte material and a preparation method and application thereof, belonging to the technical field of solid electrolytes. Background Art

[0002] With the development of the times, secondary batteries are widely used in consumer electronics, electric vehicles and large-scale energy storage systems. However, liquid electrolytes are generally used in existing secondary batteries. During the charging and discharging process, they have serious side reactions and irreversible growth of dendrites, which can easily cause short circuits, fires and even explosions. In view of the above problems, the use of solid polymer electrolytes instead of liquid electrolytes is an effective measure to solve the problem of battery safety. Compared with liquid electrolytes, solid electrolytes can fundamentally solve the problem of dendrite growth caused by ion migration due to the lack of mobile phase, which can greatly improve the battery operating current and operating temperature. Furthermore, it can also greatly extend the battery's cyclability and service life.

[0003] In the existing technology, solid electrolytes are mostly made of oxides or sulfides. When they are adapted to high-energy negative electrodes such as silicon negative electrodes and lithium metal negative electrodes, the interfacial reaction is difficult to control, and in severe cases it even affects the cycle performance of the battery. In addition, during use, in order to increase the operating pressure of the electrolyte, the solid electrolyte layer is relatively thick, which cannot reflect its energy density advantage.

[0004] Chinese patent (CN117878396A) discloses an in-situ polymerized polymer-based solid electrolyte membrane and its preparation method, wherein the polymer monomer and the fast ion conductor are dissolved in an organic reagent to obtain a mixed solution A; the organic ionic liquid and the electrolyte salt are dissolved in an organic reagent to obtain a mixed solution B; the mixed solutions A and B are mixed to obtain a polymer electrolyte layer slurry; the polymer electrolyte layer slurry is compounded with a porous matrix, in-situ polymerized and cured to obtain a polymer-based solid electrolyte membrane. However, this technical solution needs to rely on fast ion conductors to improve the elasticity and conductivity of the electrolyte on the one hand, and on the other hand, it needs to improve the mechanical properties of the electrolyte through a porous matrix. Although the ionic conductivity of the obtained electrolyte is 0.53×10 -3 Scm -1 However, it still cannot meet the requirements of solid-state batteries for electrolytes and needs further improvement and enhancement.

[0005] Asparagine polyurea has excellent mechanical properties and chemical corrosion resistance, improves the cycle stability of battery operation, and can be used as a polymer electrolyte matrix. However, asparagine polyurea-based solid polymer electrolytes have low ionic conductivity at room temperature, and the interface impedance increases due to the unstable contact between the solid electrolyte / electrode interface, resulting in poor electrochemical performance in sodium metal or sodium ion solid-state batteries. Summary of the invention

[0006] In view of the problems existing in the prior art, the first object of the present invention is to provide an asparagine polyurea-based in-situ polymer electrolyte material. The electrolyte adopts an asparagine polyurea matrix as a skeleton. Based on its excellent mechanical properties and corrosion resistance, it can effectively inhibit the growth of dendrites in the battery during charging and discharging, thereby improving the cycle life of the battery. At the same time, the asparagine polyurea contains a polyetheramine structure soft chain inside, which can complex with metal ions to improve the ionic conductivity of the material.

[0007] The second object of the present invention is to provide a method for preparing an asparagus polyurea-based in-situ polymer electrolyte material. The method adopts an in-situ polymerization process. Compared with the traditional polymer electrolyte preparation process, the in-situ polymerization process can not only effectively improve the electrolyte / electrode interface contact problem and increase the interface compatibility, but also has the advantages of simple process, reduced energy consumption, low cost, etc., and is suitable for large-scale production.

[0008] The third object of the present invention is to provide an application of an asparagine polyurea-based in-situ polymer electrolyte material as a solid electrolyte for preparing a secondary battery. The polymer electrolyte uses a liquid electrolyte as a plasticizer to ensure that ions can be quickly transferred in the swelling phase during the charge and discharge process, significantly improving the ionic conductivity of the asparagine polyurea-based polymer electrolyte, and effectively solving the problem that the ionic conductivity of the all-solid-state polymer electrolyte in the prior art is low and cannot meet the application in solid-state batteries.

[0009] In order to achieve the above technical objectives, the present invention provides an aspartic acid polyurea-based in-situ polymer electrolyte material, characterized in that: it is obtained by in-situ polymerization reaction of raw materials including polyaspartic acid ester, isocyanate curing agent and electrolyte;

[0010] The molar ratio of the amino group in the polyaspartic acid ester to the isocyanate group in the isocyanate curing agent is 1:0.8-1.2;

[0011] The mass ratio of the polyaspartic acid ester to the electrolyte is 1:1-2;

[0012] The electrolyte comprises a sodium salt, a solvent and an additive;

[0013] The solvent is at least one of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate and succinonitrile.

[0014] As a preferred solution, the polyaspartic acid ester consists of polyetheramine and diethyl maleate.

[0015] As a preferred solution, the structural formula of the polyaspartic acid ester is as follows:

[0016] Formula 1:

[0017] ;

[0018] Among them, 10≤y≤40, 3≤x+z≤8.

[0019] As a preferred solution, the isocyanate curing agent is at least one of HDI trimer, IPDI trimer and IPDI monomer.

[0020] As a preferred solution, the concentration of sodium salt in the electrolyte is 1-3 mol / L.

[0021] As a preferred solution, the sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide.

[0022] As a preferred solution, the additive is fluoroethylene carbonate.

[0023] As a preferred solution, the volume percentage of the additive in the solvent is 3-10%.

[0024] The present invention also provides a method for preparing an aspartic acid polyurea-based in-situ polymer electrolyte material, which comprises sequentially adding polyaspartic acid ester and isocyanate curing agent into an electrolyte, fully mixing to obtain a precursor solution, and then heating to perform an in-situ polymerization reaction to obtain the product.

[0025] As a preferred solution, the preparation process of the electrolyte material is carried out under a protective atmosphere.

[0026] As a preferred solution, the protective atmosphere is nitrogen and / or argon.

[0027] As a preferred solution, the in-situ polymerization reaction is carried out inside the battery under the following conditions: temperature of 50-70° C. and time of 24-72 h.

[0028] The present invention also provides an application of an asparagine polyurea-based in-situ polymer electrolyte material as a solid electrolyte for preparing a secondary battery.

[0029] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:

[0030] 1) The asparagine polyurea-based in-situ polymer electrolyte provided by the present invention adopts an asparagine polyurea matrix as a skeleton. Based on its excellent mechanical properties and corrosion resistance, it can effectively inhibit the growth of dendrites during the charge and discharge process of the battery and improve the cycle life of the battery. At the same time, the asparagine polyurea contains a polyetheramine structure soft chain inside, which can complex with metal ions and improve the ionic conductivity of the material.

[0031] 2) In the preparation method provided by the present invention, an in-situ polymerization process is adopted. Compared with the traditional polymer electrolyte preparation process, the in-situ polymerization process can not only effectively improve the electrolyte / electrode interface contact problem and increase the interface compatibility, but also has the advantages of simple process, reduced energy consumption, low cost, etc., and is suitable for large-scale production.

[0032] 3) In the technical solution provided by the present invention, the synergistic effect between the sodium salt, additives and small molecule plasticizer solvent in the liquid electrolyte can, on the one hand, efficiently dissolve the resin and curing agent, thereby ensuring the uniform distribution of the components of the asparagine polyurea in-situ electrolyte; on the other hand, it can also effectively ensure that ions can be quickly transferred in the swelling phase during the charge and discharge process, thereby significantly improving the ionic conductivity of the asparagine polyurea-based polymer electrolyte. The ionic conductivity of the obtained electrolyte can reach 1.34×10 -3 S cm -1 , which effectively solves the problem that the ionic conductivity of all-solid-state polymer electrolytes in the existing technology is low and cannot meet the application requirements in solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a state diagram of the precursor solution prepared in Example 1 and Example 3 of the present invention after solidification;

[0034] Figure 2 Graphs showing the ionic conductivity of the asparagine polyurea-based polymer electrolytes prepared in Example 1, Example 3 and Comparative Example 3 of the present invention;

[0035] Figure 3 The AC impedance spectra of the asparagine polyurea-based polymer electrolytes prepared in Example 1 and Comparative Example 3 of the present invention are shown;

[0036] Figure 4 LSV curves of the asparagine polyurea-based polymer electrolytes prepared in Examples 1 and 3 of the present invention;

[0037] Figure 5 The charge and discharge curves of the asparagine polyurea-based polymer electrolyte prepared in Examples 1 and 3 of the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described below by way of examples, but is not intended to limit the present invention.

[0039] Example 1

[0040] Material preparation:

[0041] (1) Electrolyte preparation: Dissolve a certain amount of NaClO4 in PC solvent containing 5% FEC to form 1.0 M NaClO4 in PC with 5% FEC electrolyte.

[0042] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y=39, x+z=6) to 4 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.31 g of HDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0043] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60 °C oven and heated for 72 h to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0044] Battery assembly and electrochemical testing:

[0045] The battery assembly structure corresponding to the ionic conductivity test is: negative electrode shell, gasket, electrolyte, gasket, positive electrode shell; the battery assembly structure corresponding to the interface impedance test is: negative electrode shell, gasket, sodium sheet, electrolyte, sodium sheet, gasket, positive electrode shell; the battery assembly structure corresponding to the electrochemical window test is: negative electrode shell, gasket, sodium sheet, electrolyte, gasket, positive electrode shell. The battery assembly structure corresponding to the cycle and rate performance test is: negative electrode shell, gasket, sodium sheet, electrolyte, sodium vanadium phosphate positive electrode sheet, positive electrode shell. The battery shell adopts the CR2016 model. The sodium vanadium phosphate positive electrode sheet is a mixture of sodium vanadium phosphate positive electrode material, conductive agent and binder, and coated on aluminum foil, and then heated to volatilize the solvent.

[0046] Example 2

[0047] Compared with Example 1, the difference is that the curing agent used is replaced by IPDI trimer instead of HDI trimer, as follows:

[0048] (1) Electrolyte preparation: Dissolve a certain amount of NaClO4 in PC solvent containing 5% FEC to form 1.0 M NaClO4 in PC with 5% FEC electrolyte.

[0049] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈39, x+z=6) to 4 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.602 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0050] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60 °C oven and heated for 72 h to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0051] The battery assembly and electrochemical performance test were the same as in Example 1.

[0052] Example 3

[0053] Compared with Example 1, the difference is that the molecular weight of the polyaspartic acid ester used is changed from (y≈39, x+z=6) to (y≈12.5, x+z=6), as follows:

[0054] (1) Electrolyte preparation: Dissolve a certain amount of NaClO4 in PC solvent containing 5% FEC to form 1.0 M NaClO4 in PC with 5% FEC electrolyte.

[0055] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈12.5, x+z=6) to 4 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.587 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0056] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60 °C oven and heated for 72 h to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0057] The battery assembly and electrochemical performance test were the same as in Example 1.

[0058] Example 4

[0059] Compared with Example 1, the difference is that the amount of electrolyte added is changed from 4g to 3.5g, as follows:

[0060] (1) Electrolyte preparation: Dissolve a certain amount of NaClO4 in PC solvent containing 5% FEC to form 1.0 M NaClO4 in PC with 5% FEC electrolyte.

[0061] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈39, x+z=6) to 3.5 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.31 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0062] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60°C oven and heated for 72 hours to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0063] The battery assembly and electrochemical performance test were the same as in Example 1.

[0064] Example 5

[0065] Compared with Example 1, the difference is that the electrolyte composition used is different, as follows:

[0066] (1) Electrolyte preparation: A certain amount of NaPF6 was dissolved in a mixed solvent containing EC and DEC, where the volume ratio of EC to DEC was 1:1, to form a 1.0 MNaPF6 in EC:DEC = 1:1 vol% electrolyte.

[0067] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈39, x+z=6) to 4 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.31 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0068] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60°C oven and heated for 72 hours to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0069] The battery assembly and electrochemical performance test were the same as in Example 1.

[0070] Example 6

[0071] Compared with Example 1, the difference is that the electrolyte used is replaced by 1.0 M NaClO4 in PC with 5% FEC with 1.0 M LiPF6 in DMC:EC:EMC=1:1:1 Vol%, as follows:

[0072] Electrolyte configuration: A certain amount of LiPF6 was dissolved in a mixed solvent containing EC and DEC, where the volume ratio of EC to DEC was 1:1, to form a 1.0 M LiPF6 in DMC:EC:EMC=1:1:1 Vol% electrolyte.

[0073] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈39, x+z=6) to 4 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.31 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0074] (3) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60°C oven and heated for 72 hours to solidify, thereby obtaining the asparagine polyurea-based in-situ polymer electrolyte.

[0075] Battery assembly and electrochemical testing:

[0076] The battery assembly structure corresponding to the ionic conductivity test is: negative electrode shell, gasket, electrolyte, gasket, positive electrode shell; the battery assembly structure corresponding to the interface impedance test is: negative electrode shell, gasket, lithium sheet, electrolyte, lithium sheet, gasket, positive electrode shell; the battery assembly structure corresponding to the electrochemical window test is: negative electrode shell, gasket, lithium sheet, electrolyte, gasket, positive electrode shell. The battery assembly structure corresponding to the cycle and rate performance test is: negative electrode shell, gasket, lithium sheet, electrolyte, lithium iron phosphate positive electrode sheet, positive electrode shell. The battery shell adopts the CR2016 model. The lithium iron phosphate positive electrode sheet is a mixture of lithium iron phosphate positive electrode material, conductive agent and binder, and coated on aluminum foil, and then heated to volatilize the solvent.

[0077] Comparative Example 1

[0078] Compared with Example 1, the difference is that no solvent is added, as follows:

[0079] (1) In an argon atmosphere, 2 g of polyaspartic acid ester (y≈39, x+z=6) was heated at 45 °C to melt into a liquid phase. Subsequently, 0.5 g of NaClO4 was added to the molten polyaspartic acid ester and stirred for 2 h until it was completely dissolved. Finally, 0.31 g of IPDI trimer (HT-6100) curing agent was added and stirred until a precursor solution was uniformly formed.

[0080] (2) During the battery assembly process, 50 ul of the precursor solution was dripped onto both sides of the glass fiber separator to completely soak the separator. After the assembly was completed, the battery was placed in a 60 °C oven and heated for 24 h to solidify, thereby obtaining an asparagine polyurea-based in-situ solid polymer electrolyte.

[0081] The battery assembly and electrochemical performance test were the same as in Example 1.

[0082] Comparative Example 2

[0083] Compared with Example 1, the difference is that the asparagine polyurea-based polymer electrolyte is prepared by blade coating, as follows:

[0084] (1) Electrolyte preparation: Dissolve a certain amount of NaClO4 in PC solvent containing 5% FEC to form 1.0 M NaClO4 in PC with 5% FEC electrolyte.

[0085] (2) Under argon atmosphere, add 2 g of polyaspartic acid ester (y≈39, x+z=6) to 3 g of the prepared electrolyte, stir thoroughly until dissolved, then add 0.31 g of IPDI trimer (HT-6100) and stir for 2 h to obtain a precursor solution.

[0086] (3) The precursor solution was evenly coated onto a glass plate using a scraper, and the solution was placed in a vacuum oven at 60°C and heated for 72 h until solidified to obtain an asparagine polyurea-based polymer electrolyte.

[0087] The battery assembly and electrochemical performance test were the same as in Example 1.

[0088] Comparative Example 3

[0089] Compared with Example 1, the difference is that no solvent is added and the asparagine polyurea-based solid polymer electrolyte is prepared by blade coating, as follows:

[0090] (1) In an argon atmosphere, 2 g of polyaspartic acid ester (y≈39, x+z=6) was heated at 45 °C to melt into a liquid phase. Subsequently, 0.5 g of NaClO4 was added to the molten polyaspartic acid ester and stirred for 2 h until it was completely dissolved. Finally, 0.31 g of IPDI trimer (HT-6100) curing agent was added and stirred until a precursor solution was uniformly formed.

[0091] (2) The precursor solution was evenly scraped onto a glass plate using a scraper, and the solution was placed in a vacuum oven at 60°C and heated for 24 h until solidified to obtain an asparagine polyurea-based solid polymer electrolyte.

[0092] The battery assembly and electrochemical performance test were the same as in Example 1.

[0093] According to the present embodiment, a polyurea-based in-situ polymer electrolyte material and its preparation method and application are provided. Figure 1 As shown, the precursor solutions obtained in Example 1 and Example 3 were heated at 60°C for 72 hours to form a transparent slightly yellowish gel polymer electrolyte. Due to the plasticizing effect of the electrolyte, the ionic conductivity was significantly improved compared with that of Comparative Example 3. Figure 2 As shown in Figure 2, the ionic conductivity of the polymer electrolytes prepared in Example 1 and Example 3 reached 1.34×10 -3 S cm -1 and 9.26×10 -4 S cm -1 , while the conductivity of the polymer electrolyte prepared in Comparative Example 3 is only 1.72×10 -5 Scm -1 In addition, compared with the traditional preparation method of polymer electrolytes, the in-situ preparation process can effectively improve the electrolyte / electrode interface compatibility and reduce the interface impedance. Figure 3As shown, the interfacial impedance of the in-situ polymer electrolyte prepared in Example 1 is reduced by two orders of magnitude compared with that in Comparative Example 1. In order to evaluate the electrochemical stability of the aspartame polyurea in-situ polymer electrolyte, the LSV curves of the polymer electrolytes prepared in Example 1 and Example 3 show that the electrochemical stability window ( Figure 4 ). The application of polymer electrolytes in sodium solid-state batteries was evaluated by preparing sodium vanadium phosphate NVP positive electrode and assembling NVP / Na half-cell, such as Figure 5 As shown in Figure 1, the discharge capacity of the sodium solid-state battery 1C assembled with the polymer electrolyte prepared in Example 1 is 104.28 mAh g -1 The first cycle charge and discharge efficiency is 99.53%, and the discharge capacity of the sodium solid-state battery assembled with the polymer electrolyte prepared in Example 3 is 102.55 mAh g -1 The first cycle charge and discharge efficiency is 99.6%, and after 200 cycles, the capacity retention rate can still reach more than 98%. In addition, the application of polyurea-based in-situ polymer electrolytes in other solid-state metal batteries is also verified. The ionic conductivity of the lithium-based polymer electrolyte prepared in Example 6 is 1.67×10 -3 S cm -1 At the same time, the discharge capacity of the assembled lithium solid-state battery at 1 C reached 157.6 mAh / g, and the capacity retention rate was 91% after 100 cycles. Therefore, the prepared asparagus polyurea-based in-situ polymer electrolyte can meet the application requirements in solid-state metal batteries.

[0094] In summary, the asparagus polyurea-based in-situ polymer electrolyte material provided by the present invention realizes the application in solid-state metal batteries through an in-situ polymerization preparation process and obtains excellent electrochemical properties.

Claims

1. An asparagine polyurea-based in-situ polymer electrolyte material, characterized in that: Obtained by in-situ polymerization of raw materials including polyaspartic acid ester, isocyanate curing agent and electrolyte; The molar ratio of the amino group in the polyaspartic acid ester to the isocyanate group in the isocyanate curing agent is 1:0.8-1.2; The polyaspartic acid ester is composed of polyetheramine and diethyl maleate; The mass ratio of the polyaspartic acid ester to the electrolyte is 1:1-2; The electrolyte comprises sodium salt, solvent and additive; the concentration of sodium salt in the electrolyte is 1-3 mol / L; The additive is fluoroethylene carbonate; The solvent is at least one of propylene carbonate, ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate; The preparation method of the electrolyte material is as follows: polyaspartic acid ester and isocyanate curing agent are sequentially added into the electrolyte, fully mixed to obtain a precursor solution, and then heated to perform in-situ polymerization reaction to obtain the electrolyte material.

2. The asparagine polyurea-based in-situ polymer electrolyte material according to claim 1, characterized in that: The isocyanate curing agent is at least one of HDI trimer, IPDI trimer and IPDI monomer.

3. The asparagine polyurea-based in-situ polymer electrolyte material according to claim 1, characterized in that: The sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide.

4. The asparagine polyurea-based in-situ polymer electrolyte material according to claim 1, characterized in that: The volume percentage of the additive in the solvent is 3-10%.

5. The asparagine polyurea-based in-situ polymer electrolyte material according to claim 1, characterized in that: The preparation process of the electrolyte material is carried out under a protective atmosphere; the in-situ polymerization reaction is carried out inside the battery under the following conditions: temperature of 50-70° C. and time of 24-72 hours.

6. The use of an asparagine polyurea-based in-situ polymer electrolyte material according to any one of claims 1 to 5, characterized in that: As a solid electrolyte for preparing secondary batteries.

Citation Information

Patent Citations

  • In-situ polymerized polymer-based solid electrolyte membrane and preparation method thereof

    CN117878396A

  • Polyurea-based solid polymer electrolyte and preparation method thereof

    CN114478985A

  • Polyurea-based solid electrolyte and preparation method thereof

    US11996211B1